Kaunseling Kelompok Terapi Kognitif dalam Pengurusan Stres dalam kalangan Polis - Wan Anor Wan Sulaiman; Wan Nurfatini Wan Anor; Adi Fahrudin; Mohd Dahlan Hj. A. Malek (2018)
This article was written to discuss the use ofcognitive therapy group counseling method in stress managementamong police personnel in Malaysia. It also discusses what police stressscenarios, stress factors, stress effects experienced by policemen in their work and lifestyle, and how existing programs have been done to reduce police stress. The results of this paper can give an idea and suggestion to the Royal Malaysian Police (PDRM)in intervention using cognitivecounseling group interventions as a method that can be applied to high-stresspolice personnel in particular and who experience moderate stress.